Al-Medina Al-Munawwarah in the writings of Arab travelers | المدينة المنورة في كتابات الرحالة العرب - Al Juhani | الجهني, Laila Said Swailem | ليلى سعيد سويلم (Al-Madinah Al-Munawwarah Research and Studies Center | مركز بحوث ودراسات المدينة المنورة, 2023)
The researcher points out that the Arabs knew the trip before Islam, so one of their most famous trips was the winter and summer trip, and with the advent of the Islamic call, new motivations for the trip appeared, such as the call, jihad and visiting the three mosques, but the religious motivation from the Hajj trip remained the first driver of the trips, which affected the literature Trips, and helped its development, which made the Two Holy Sanctuaries the focus of the travelers' attention during their visit, with a difference in goals and objectives. The trips provide us with a large amount of information about the political, economic, social and security reality of these two cities, and also provide us with translations of scholars whose translation books did not provide them with their right. Therefore, the researcher will present the most important trips that took place to the Two Holy Mosques, talking about the journey of Ibn Jubayr, introducing him, and touching on some of his qualities, as well as presenting his approach and its impact on the transfer of the course of his trip, and then move on to his visit to the city, which lasted only five days from the duration of his trip. His interest in some aspects of the city, such as the Prophet’s Mosque, the scenes, Al-Baqi’, and Uhud, with some references and allusions to other urban features, such as the walls and doors. For the expansion of the Abbasid Caliph al-Mahdi in 161 AH to the Haram, he conveyed his accurate description of it, then moved to what he mentioned of mosques and archaeological monuments that the city contains, such as the scenes of some of the Companions, their mosques and their roles, as well as what he saw inside the Prophet’s Mosque and the actions that take place in it by the preacher and the worshipers, in an attempt From it to transfer the religious, scientific and political reality inside the mosque in that period. | تُشير الباحثة إلى أن العرب عرفوا الرحلة من قبل الإسلام ، فكان من أشهر رحلاتهم رحلة الشتاء والصيف ، ومع ظهور الدعوة الإسلامية ظهرت بواعث جديدة للرحلة ، كالدعوة والجهاد وزيارة المساجد الثلاثة ، ولكن الباعث الديني من رحلة الحج ظل هو المحرك الأول للرحلات ، مما أثر في أدب الرحلات ، وساعد على تطوره ، مما جعل الحرمان الشريفان محط اهتمام الرحالة أثناء زيارتهم ، مع تباين في الأهداف والمقاصد ، فالرحلات تُقدم لنا كماً كبيراً من المعلومات عن الواقع السياسي والاقتصادي والاجتماعي والأمني لهاتين المدينتين ، كما وتزودنا بتراجم للعلماء الذين لم توفهم حقهم كتب التراجم. ولذلك فإن الباحثة ستقوم بعرض لأهم الرحلات التي قامت إلى الحرمين الشريفين ، فتتحدث عن رحلة ابن جبير ، فتُعرِّف به ، وتتطرق لبعض صفاته ،كما وتعرض لمنهجه وأثره في نقل مجريات رحلته ، ثم تنتقل إلى زيارته للمدينة والتي دامت خمسة أيام فقط من مدة رحلته ، فتذكر اهتمامه ببعض النواحي في المدينة كالمسجد النبوي، والمشاهد ، والبقيع ، وأحد ، مع بعض الإشارات والتلميحات لملامح عمرانية أخرى ، كالسور والأبواب ، ثم تذكر تتبعه لمصادر المياه في المدينة ، وحديثه عن الأوضاع الاقتصادية والاجتماعية وبعض العادات التي اتصف بها أهل المدينة ، كما وتتحدث عن وصفه لتوسعة الخليفة العباسي المهدي سنة 161هـ للحرم فتنقل وصفه الدقيق لها، ثم تنتقل إلى ما ذكره من المساجد والمعالم الأثرية التي تحتويها المدينة ، كمشاهد بعض الصحابة ومساجدهم ودورهم ، كما وتذكر ما شاهده داخل المسجد النبوي وما يقع فيه من تصرفات من قبل الخطيب والمصليين ، في محاولةٍ منه لنقل للواقع الديني والعلمي والسياسي داخل المسجد في تلك الفترة .